2018
DOI: 10.1080/15321819.2017.1407339
|View full text |Cite
|
Sign up to set email alerts
|

About molecular profile of lung cancer in Tunisian patients

Abstract: This study made us wonder about the possibility of implementing molecular techniques in low-income countries and about the necessity of optimizing the financial resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…ALK rearrangement was usually associated with young age, female gender, and a no- or light-smoking history [47,49]. A Tunisian study by Mezni et al [50] showed a prevalence of ALK rearrangement in six (7.14%) out of 84 patients using IHC, which differs fairly substantially from our findings. Furthermore, Liang et al [51] suggested that the incidence of ALK rearrangement in the Chinese population may be correlated with smoking status as they observed a lower prevalence in smokers (2.9%) than in non-smokers (7.2%).…”
Section: Discussioncontrasting
confidence: 74%
“…ALK rearrangement was usually associated with young age, female gender, and a no- or light-smoking history [47,49]. A Tunisian study by Mezni et al [50] showed a prevalence of ALK rearrangement in six (7.14%) out of 84 patients using IHC, which differs fairly substantially from our findings. Furthermore, Liang et al [51] suggested that the incidence of ALK rearrangement in the Chinese population may be correlated with smoking status as they observed a lower prevalence in smokers (2.9%) than in non-smokers (7.2%).…”
Section: Discussioncontrasting
confidence: 74%
“…Regarding the “classic” mutations such as deletion in exon 19 and p.L858R, we found that 23.5% of our patients carried deletion in exon 19, which is in line with data from previous studies including those conducted on Tunisian patients [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, the p.L858R was identified in only four patients (11.7%), confirming once again the particularity of our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, while Mraihi et al found 44% EGFR positive samples using IHC, Dhieb et al reported only one sample with the E746-A750 del19 mutation, using the same technique [ 26 , 27 ]. Another study evaluating the molecular profile of 87 NSCLC samples by qPCR or NGS found that 18.4% of patients had EGFR activating mutations (12 cases with the exon 19 deletions and 4 patients carrying the p.L858R) [ 28 ]. In addition, Arfaoui et al showed that 3 out of the 26 analyzed samples harbor two sensitizing mutations (exon 19 deletion and p.G719X) and one exon 20 insertion associated with de novo resistance to targeted EGFR inhibitors and correlate with a poor patient prognosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations